The Role of Emerging Technologies of Students' Academic Achievement at Polytechnic Seberang Perai - Omar, Nurul Ihsaniah; Ibrahim, Mohammad Noor (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2024)
Education is crucial for global progress and is always changing due to the impact of current technologies. Ongoing discussions focus on how developing technologies are affecting teaching and learning approaches. This essay examines how incorporating new technology in education impacts academic success. Although technology is deemed essential for information dissemination in education, the influence of new technology on academic success is still uncertain. This research examines the elevated failure rates at Seberang Perai Polytechnic (PSP) in Malaysia, linking them to factors including insufficient information, slow progress in studies, and inadequate time management. The study seeks to investigate the influence of new technologies on academic achievement at PSP. The study uses an ex post facto research strategy and quantitative approaches to gather data from 200 respondents at PSP. The study aims to identify the new technologies used by students in various departments and evaluate how these technologies affect academic achievement. Chi-Square analysis and Spearman correlation coefficient are used to test hypotheses. The survey shows that modern technology is widely accessible, with cellphones being the most favored among pupils. Noticeable discrepancies in technological access across departments have been discovered. Weak connections exist between technology usage frequency and academic achievement, with just one statistically meaningful association discovered in obtaining material on the internet. The research helps fill the void in literature on the use of new technologies for academic objectives within the context of PSP. The results underscore the need of teaching students about efficient technology utilization to improve academic results. The study highlights that the presence of new technologies does not automatically lead to academic progress. Academic improvement relies on how students incorporate these resources into their learning methods. Suggestions involve teaching students how to use technology effectively and understanding that academic success is not guaranteed solely by using technology.